Positive experience of the usage of Rituximab in management of refractory myasthenia gravis in Russia - N. I. Shcherbakova (Nervno-Myšečnye Bolezni, 2015)
A subset of patients (15 to 20%) with myasthenia gravis (MG) remains refractory to standard types of treatment. Analysis of efficiency of rituximab, a chimeric monoclonal antibody to surface antigen of B lymphocytes (CD20), in 16 patients suffering from refractory MG was performed. In all cases, the drug was injected weekly and intravenously in the dosage of 375 mg/m2, for 4 weeks. All patients were dependent on intake of corticosteroids and cyclosporin. During rituximab therapy, the gradation of MG has significantly changed, being transformed from severe forms (IV and V MGFA class) into moderate and mild forms (III, II, and I MGFA class). Improvement of the clinical state included cease of myasthenic exacerbation, increased respiratory muscle strength; significant reduction of dosages (and even canceling) of basic pathogenetic and symptomatic treatment. Complete remission with cancellation of basic therapy was recorded in 4 (25 %) of patients within 2-year period. However, 2 of them manifested with aggravation of MG after the first course of rituximab, in 9 and 24 months, correspondingly, which required resumption of corticosteroid therapy and repeating of courses of rituximab, with positive result. In 9 (56.25 %) cases, pharmacological remission was recorded; in 3 (18.75 %) cases, there was a significant improvement of initially severe forms. In all patients rituximab therapy lead to the clinical improvement: prior to completion of the course, after the 1st and the 2nd infusion - in 12 (75 %) patients; 1 to 3 weeks after completion of the course – in 4 (25 %) patients. Maximal improvement was registered in 1 to 12 month after completion of the course of rituximab intake (at the terms of 4. ± 2.0 months). There were the following stages of basic therapy cancellation: during first 1 to 3 months of rituximab treatment, pyridostigmine and cyclosporine were cancelled; corticosteroids were dropped off gradually, according to the clinical status of patients. Increased sensitivity to steroids, even in small dosages, was recorded. Infusion reactions were dose-related and most frequently occurred during first administration of rituximab and were eliminated with slowing down of the infusion rate. Infusion reactions and side effects were absent in the course of postinfusion period in 5 (31.25 %) and 8 (50 %) patients, correspondingly.